The control of the tricarboxylic acid cycle in the North American eel, Anguilla rostrata. - Ouellet, Gabriel. (University of Ottawa (Canada), 1977)
In the North American eel, Anguilla rostrata, the problems of intracellular location of isocitrate oxidation and the control of the tricarboxylic acid (TCA) cycle in the liver were investigated. Three methods were used to elucidate these problems. The first method involved the determination of isolated mitochondrial oxidative capacity with different TCA cycle intermediates measured by the Clark oxygen electrode; isocitrate was oxidized at a rate comparable to the subsequent TCA cycle intermediates (∝ ketoglutarate, succinate and malate) showing that these isolated particles are able to maintain isocitrate oxidation. However, pyruvate oxidative rate was significantly lower than isocitrate, and citrate and acetate were not oxidized alone or in conjunction with malate or oxaloacetate. The second method dealt with the incorporation of a radioactive substrate into the isolated mitochondria and the analysis of the distribution of this label in the TCA cycle intermediates. Labelled citrate was used with added aconitase. Results demonstrated that isocitrate was mobilized in the isolated mitochondria with label accumulation in the subsequent TCA cycle intermediates. This experiment suggested that isolated intact eel liver mitochondria contain all the enzymes necessary for the complete oxidation of isocitrate by the TCA cycle. The third method was the spectrophotometric and oxygen electrode analyses of specific activities and compartmentalization of enzymes necessary for the TCA cycle. Results demonstrated that citrate synthase (CS) and transhydrogenase activities were found only in the mitochondrial fraction; aconitase was detected only in the supernatant; and NADP-specific isocitrate dehydrogenase (NADP-IDH) and glutamate dehydrogenase (GDH) were measured in both fractions. NAD-IDH was not detected using a number of isolation procedures. Since CS and transhydrogenase activities were lower than those of NADP-IDH, these two enzymes probably limit metabolic flux through the TCA cycle in eel liver. From these data, a proposal for the physiological significance and the control mechanism of the TCA cycle in the eel liver is discussed, with isocitrate oxidation occurring either within the mitochondrial or cytoplasmic compartments depending upon the NADP/NADPH ratio and/or the energy status of the cell.
Keywords: Biology, Zoology.